Models of Spatial Polarities in Jamal Abu Hamdan’s Novels - Al-Shamali, Nidal; Al-Khateeb, Abdallah (Dirasat: Human and Social Sciences, 2023)
The researchers’ interest in the setting and especially the element of place in the novel has long been discussed in relation to narrative discourse. The significance of place has surpassed its importance as an element of the plot to its connotative implications. Narrative space goes beyond a mere description of the surrounding setting to create polarities in relation to other harmonious elements. Juri Lotman refers to this relationship between literary space and other narrative elements as spatial polarity. Spatial polarity cannot be realized in isolation from other narrative elements such as time, characters, and events. Once narrative space has been exploited as a functional narrative element, it creates paradoxical semiotic significance which foreshadows other textual, geographic, referential, and functional significance. By analyzing the narrative blog by Jamal Abu Hamdan, the researchers introduce a study of spatial models and spatial polarities in Hamdan’s novels from a semiotic point of view.